Influence of atmospheric nitric oxide concentration on the measurement of nitric oxide in exhaled air. Issue 8 (1st August 1998) - Corradi, Massimo; Pelizzoni, Alessandro; Majori, Maria; Cuomo, Angelo; Munari, Eriberto de'; Pesci, Alberto
Abstract : BACKGROUND: Measurement of nitric oxide (NO) in exhaled air shows promise as a non-invasive method of detecting lung inflammation. However, variable concentrations of NO are measured in environmental air. The aim of this study was to verify a possible relationship between exhaled NO and atmospheric NO values during high atmospheric NO days. METHOD: Exhaled air from 78 healthy non-smokers of mean age 35.3 years was examined for the presence of NO using a chemiluminescence NO analyser and NO levels were expressed as part per billion (ppb). The exhaled air from all the subjects was collected into a single bag and into two sequential bags. Before each test atmospheric NO was measured. RESULTS: The mean (SE) concentration of exhaled NO collected into the single bag was 17.1 (0.6) ppb while the mean values of exhaled NO in bags 1 and 2 were 16.7 (1.3) ppb and 13.8 (1.2) ppb, respectively. The atmospheric NO concentrations registered before each test varied from 0.4 to 71 ppb. There was a significant correlation between exhaled NO in the single bag and atmospheric NO ( r = 0.38, p = 0.001). The atmospheric NO concentration also correlated with exhaled NO both in bag 1 ( r = 0.44, p = 0.0001) and in bag 2 ( r = 0.42, p = 0.0001). These correlations disappeared with atmospheric NO concentrations lower than 35 ppb. CONCLUSIONS: These results indicate a relationship between atmospheric NO and NO levels measured in exhaled air, therefore exhaled NO should not be measured on very high atmospheric NO days.